The obstacles of implementing private finance initiatives in local government in Malaysia / Maryadi Hasan and Dani Salleh - Hasan, Maryadi; Salleh, Dani (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
Since its introduction in Malaysia, the Private Finance Initiative (PFI) Model has leveraged the government as a form of alternative procurement, primarily to reduce government spending, and to provide public infrastructure more efficiently and effectively. Although the PFI is said to be an efficient model for the implementation of public procurement policies, at the local authority (LAs) level, it is seen less considered. The PFI’s procurement method is seen at its initial stage although this model has long been introduced in Malaysia in the ninth Malaysia Plan (2006-2010). This article aims to examine the obstacles on the implementation of PFIs in LAs in Malaysia. In order to achieve the objective of the study, literature review was examined, as well as reports of either government documents or the major reports on the implementation of PFIs in Malaysia were analyzed. The results of the study found that there were mixed views on the adoption of the PFI model as a government procurement strategy in LAs in Malaysia. Implementation of PFIs in LA in Malaysia is seen to have issues related to management, administration, leadership, expertise, knowledge, and experience in managing PFI projects. As recommendations of the study, it is stressed that various parties such as government at various levels, private companies, and researchers should pay attention and take urgent measures if LAs want to be involved in the implementation of the PFI project. LAs also need to be active in exploring new rules and strategies in diversifying their earnings. As a future research proposal, it is important to identify the current private financing method adopted at the LAs. In addition, future research also need to identify the level of awareness, experience, and knowledge of the PFI project in LA, as well as the factors affecting its implementation at the local level are also important.